A Bridge Too Far? Real‐World Practice Patterns of Early Glucocorticoid Use in the Canadian Early Arthritis Cohort. Issue 1 (28th October 2021) - Andersen, Kathleen M.; Schieir, Orit; Valois, Marie‐France; Bartlett, Susan J.; Bessette, Louis; Boire, Gilles; Haraoui, Boulos; Hazlewood, Glen; Hitchon, Carol; Keystone, Edward C.; Pope, Janet; Tin, Diane; et al.
Abstract : Objective: To describe patterns of glucocorticoid use in a large real‐world cohort with early rheumatoid arthritis (RA) and assess the impact on disease activity and treatment. Methods: Data are from adults with new RA (≤1 year) recruited to the Canadian Early Arthritis Cohort (CATCH) and are stratified on the basis of whether a person was prescribed oral glucocorticoids within 3 months of study entry. Disease activity was compared over 24 months. Mixed‐effects logistic regression was used for adjusted odds ratios (aORs) of escalation to biologics separately for 12 and 24 months, with random effects terms to account for prescribing patterns clustering by study site. Results: Among 1891 persons, 30% received oral steroids. Users were older, were less often employed, and had shorter disease duration and higher disease activity. Disease activity improved over time, with early glucocorticoid users starting at higher levels of disease activity. Participants with early oral glucocorticoids were more likely to be on a biologic at 12 months (aOR = 2.4; 95% confidence interval [CI], 1.5‐3.7) and 24 months (aOR = 1.9; 95% CI, 1.3‐3.0). Despite Canadian clinical practice guidelines to limit corticosteroid use to short‐term or 'bridge' therapy, 30% of patients who used oral glucocorticoids still used them 2 years later. Conclusion: Early steroids were prescribed sparingly in CATCH and were often indicative of more active baseline disease as well as the need for progression to biologics.